Oral small-molecule GLP-1 receptor agonists: a new Frontier in cardiometabolic medicine - Jinkai Guo; Hua Chen (Frontiers in Pharmacology, 2026)
Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) have revolutionized the management of type 2 diabetes (T2D) and obesity, with injectable agents demonstrating significant cardiovascular (CV) risk reduction in pivotal trials including LEADER, SELECT, and SUMMIT. However, the reliance on injectable peptide formulations has constrained global accessibility and long-term adherence. The recent emergence of orally bioavailable, nonpeptide, small-molecule GLP-1 RAs—exemplified by orforglipron (Foundayo), danuglipron, and other investigational candidates—marks a paradigm shift in incretin-based therapy. Unlike oral semaglutide, which delivers a peptide via sodium N-[8-(2-hydroxybenzoyl) amino] caprylate (SNAC)-mediated absorption with stringent dosing requirements, small-molecule GLP-1 RAs evade enzymatic degradation and facilitate once-daily oral dosing without fasting restrictions or cold-chain logistics. This review synthesizes the pharmacology, Phase 3 clinical evidence (including the ACHIEVE and ATTAIN programs), comparative efficacy against injectable GLP-1 RAs and SGLT2 inhibitors, safety data from over 11,000 patients, and the evolving regulatory landscape—including FDA approval of orforglipron (Foundayo) for chronic weight management in April 2026. We explore positioning within the cardiometabolic treatment algorithm, emphasize limits of indirect comparisons, identify the unresolved cardiovascular outcomes question linked to biased partial agonism, and discuss implications for global access.